Positive negative game application design based on the Montessori method as a means of improving the mathematical connection ability of students with ADHD - Utin Desy Susiaty; Muhamad Firdaus (Jurnal Pendidikan Informatika dan Sains, 2026)
The objectives of the study are: 1) to develop a positive negative game application based on the Montessori method to improve the mathematical connection skills of students with ADHD, 2) to determine the characteristics of the mathematical connection skills of students with ADHD, and 3) to determine the mathematical connection skills of students with ADHD after using the developed positive negative game application based on the Montessori method. The method of this study is R&D with the ADDIE model. The findings in this study obtained that the results of the assessment of the three material and media experts with an average percentage of 76.32 valid criteria. From the results of trials conducted on 7 students with ADHD from SLB C Dharma Asih Pontianak, the results obtained were 96.88 for the class teacher's response, the percentage for the response of students with ADHD was 75.89 and 86.38 for the overall average with the criteria "very practical". Based on calculations related to classical completeness, 6 students were obtained complete and 1 student did not complete with the KKM of mathematics subjects set for Phase D level (equivalent to junior high school) in SLB C for Mentally Disabled, namely 65. Furthermore, the effectiveness result was 85.71% with a very effective category. This means that the Positive Negative Game Application Based on the Montessori Method is effective. The conclusions in this study are: 1) Based on the results of the validity, practicality, and effectiveness values, the Design of the Positive Negative Game Application Based on the Montessori Method developed is suitable for use. 2) the characteristics of the mathematical connection abilities of students with ADHD are already in the category of classically complete students from a total of 7 students who worked on the posttest questions. 3) the mathematical connection abilities of students with ADHD after using the Positive Negative Game Application Based on the Montessori Method experienced classical completeness which showed an increase.